2022
DOI: 10.3390/biomedicines10020479
|View full text |Cite
|
Sign up to set email alerts
|

A Novel 2-Hit Zebrafish Model to Study Early Pathogenesis of Non-Alcoholic Fatty Liver Disease

Abstract: Nonalcoholic fatty liver disease (NAFLD) is one of the most common liver diseases in adults. NAFLD progresses from benign liver fat accumulation to liver inflammation and cirrhosis, and ultimately leads to liver failure. Although several rodent models have been established for studying NAFLD, they have limitations that include cost, speed of disease development, key dissimilarities, and poor amenability to pharmacological screens. Here, we present a novel 2-hit zebrafish model to replicate aspects of NAFLD pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 45 publications
1
7
0
Order By: Relevance
“…Consistent with prior studies, HFD feeding caused a significant increase in the number of macrophages observed within the liver boundaries ( Fig. 3 D ) ( 22 ). Importantly, upon HFD-feeding, the number of macrophages per sampled liver area was significantly reduced in the embryos injected with the ltb4r2a MO compared to the non-injected controls ( Fig.…”
Section: Resultssupporting
confidence: 91%
See 2 more Smart Citations
“…Consistent with prior studies, HFD feeding caused a significant increase in the number of macrophages observed within the liver boundaries ( Fig. 3 D ) ( 22 ). Importantly, upon HFD-feeding, the number of macrophages per sampled liver area was significantly reduced in the embryos injected with the ltb4r2a MO compared to the non-injected controls ( Fig.…”
Section: Resultssupporting
confidence: 91%
“…In a second model of inflammation, we fed zebrafish embryos with a high-fat diet (HFD) consisting of a 5% homogenized egg solution at 3 and 4 dpf ( Fig. 3 C ), which leads to lipid accumulation and a mild inflammatory state that promotes macrophage infiltration into the liver parenchyma ( 22 ). Consistent with prior studies, HFD feeding caused a significant increase in the number of macrophages observed within the liver boundaries ( Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…NAFLD can be classi ed as simple steatosis (NAFL) and nonalcoholic steatohepatitis (NASH) and has tended to become epidemic in children worldwide in the last decade [11] . Although the pathogenesis of NAFLD is still unclear, the "2-hit hypothesis" is widely accepted [12] . The theory suggests that suboptimal conditions and adaptations in early development ( rst-hit) may lay the foundation for long-term susceptibility to subsequent adverse events (second-hit), which may occur in the foetus or later life, leading to more extreme outcomes or phenotypes [13] .…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, new reliable models displaying identical liver phenotypes to humans are needed. In this issue, interesting novel preclinical models are evaluated, including a guinea pig disease model, chimeric mice with humanized livers, and a novel 2-hit zebrafish model to specifically model the early pathogenesis of NAFLD [ 9 , 10 , 11 ].…”
mentioning
confidence: 99%